Evaluating the effectiveness of Baker's procedure in restoring functionality in neglected Achilles tendon injuries - Hossain, Mohammad Sabbir; Shahiduzzaman, Muhammad; Hossain, M. Shahadat; Rahman, Mohammad Anisur (International Journal of Research in Orthopaedics, 2024)
Background: Neglected Achilles tendon injuries present a significant challenge in orthopedic practice, often requiring complex surgical interventions for effective treatment. This study aims to evaluate the functional outcomes of patients with neglected Achilles tendon injuries treated using Baker's procedure, a surgical technique designed for complex cases. Methods: This prospective interventional study was conducted at multiple medical centers in Dhaka, Bangladesh, from January 1, 2012, to May 31, 2013. It included 42 patients aged 18 to 60 years with signs of old Tendo-Achilles rupture. Participants were selected based on specific inclusion and exclusion criteria and underwent Baker's Procedure. Postoperative assessments included pain levels, ankle stiffness, calf-muscle weakness, footwear restrictions, range of motion, and patient satisfaction, evaluated using the Juhana Leppilahti modified score. Result: The majority of patients (85.71%) reported no pain post-treatment, while 14.29% experienced mild pain. Ankle stiffness was absent in 71.43% of the patients and mild in 28.57%. Calf-muscle weakness varied, with 64.29% showing no weakness, 28.57% mild weakness, and 7.14% moderate weakness. Footwear restrictions were minimal, with 92.86% reporting no restrictions. Active range of motion was normal (≤5°) in 64.29% of patients and mildly limited (6-10°) in 35.71%. Patient satisfaction was high, with 71.43% being 'Very satisfied' with their treatment outcomes. Conclusions: The study demonstrates that Baker's Procedure is an effective surgical intervention for neglected Achilles tendon injuries, leading to significant pain relief, restored functional mobility, and high patient satisfaction. These findings suggest that with appropriate surgical and rehabilitative care, patients with complex Achilles tendon injuries can achieve favorable outcomes, emphasizing the importance of tailored surgical approaches in orthopedic practice.